Product variety and demand uncertainty - Dennis W. Carlton; James D. Dana (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2005)
We demonstrate that demand uncertainty alone can lead to equilibrium product variety. We consider a simple environment in which when demand is certain, a social planner, a competitive market, and a monopolist would all offer a single product, but when demand is uncertain, a social planner, a competitive market, and a monopolist will all offer vertically differentiated products. When a firm anticipates that its inventory or capacity may not be fully utilized, increasing product variety is efficient because it reduces the expected costs of excess capacity. We find that when the firm offers a continuum of product varieties, the highest quality product has the highest profit margins but the lowest percentage margin, while the lowest quality product has the highest percentage margin but the lowest absolute margin. We derive these results in both a monopoly model and a variety of different competitive models. We conclude with a discussion of empirical predictions together with a brief discussion of supporting evidence available from marketing studies.
Keywords: 330